Self-directed propulsion of an unconstrained flapping swimmer at low Reynolds number: hydrodynamic behaviour and scaling laws. (26th November 2020) - Lin, Xingjian; Wu, Jie; Zhang, Tongwei
Abstract: Abstract : Flapping-wing-based propulsion is ubiquitous in Nature, and it is free in all directions. In this work, the hydrodynamic behaviour of an unconstrained flapping foil, which can self-propel in both longitudinal and lateral directions, is numerically studied. It is found that the flapping foil can keep self-propelling in a straight line along the longitudinal direction, together with a passive oscillation in the lateral direction. Moreover, the effects of multiple parameters on the performance of the flapping swimmer are investigated, including the flapping frequency and amplitude, the mass ratio between foil and fluid, and the thickness–chord ratio of the foil. It is shown that the propulsive speed, the power consumption and the lateral oscillating motion obey some simple scaling laws. The results obtained here may provide some light on understanding biological flapping-wing-based propulsion.